Predictors of electronic health record (EHR) portal registration and frequency of portal use among patients with cancer prior to engagement in the IMPACT Consortium symptom management trials. Issue 28 (1st October 2022) - Griffin, Joan M.; Wong, Sandra L.; Yanez, Betina; Kroner, Barbara; Preiss, Liliana; Jensen, Roxanne E.; Wilder Smith, Ashley; Popovic, Jennifer; Austin, Jessica; Flores, Ann Marie; Mitchell, Sandra; Bian, Jessica; et al.
Abstract : 419 Background: The patient portal is part of an electronic health record (EHR) that allows patients to communicate with their healthcare team. The portal also provides a platform for patients to receive and complete symptom surveys that can be directly integrated into the EHR, allowing clinical care teams to monitor symptoms and provide cancer symptom management. The Improving Management of symPtoms during And following Cancer Treatment (IMPACT) consortium, supported by the National Cancer Institute's Cancer Moonshot SM, aims to improve symptom control for cancer patients through assessment and symptom management interventions deployed via the EHR. This initiative presents an opportunity to examine portal enrollment and variation in use, factors critical to successful implementation, especially among groups that have high cancer symptom burden. To this end, we examine: 1) relationships between portal enrollment prior to the launch of IMPACT interventions and neighborhood broadband access, demographic, and social characteristics; and 2) frequency of pre-intervention portal use for any purpose among enrollees. Methods: Data are derived from two of three IMPACT research centers. Enrollment in and frequency of portal use, mode of accessing the portal (web vs. phone), social, demographic, and cultural factors were extracted from the EHR. Rural Urban Commuting Area (RUCA) codes were used to classify population density and degree of rurality. Broadband access was estimated using 2015-2019 American Community Survey estimates matched to zip codes from enrolled IMPACT patients and classified as a patient's residence being in a community with high (≥85% of households) or low (< 85% of households) access. Bivariate comparisons and adjusted odds ratios were used to describe all associations. Results: Forty-seven percent of patients (22, 596/48, 034) were enrolled in the portal prior to the intervention. Patients in zip codes with low broadband access and those who were men, > 65 years old, not White, of Hispanic ethnicity, or disabled or not employed had significantly lower odds of being enrolled in the portal. If enrolled, 21% (n = 4825) used the portal at least once a week. Less variation was found in the average frequency of portal use, but patients younger than 40, and those who were Black, disabled, unemployed, or those who used a mobile device to access the portal had the lowest odds of accessing it at least once a week. Conclusions: Significant disparities in portal enrollment exist across demographic groups and among those with limited broadband access. Among those enrolled, most used the portal less than once a week. Fewer differences in frequency of use were observed by sociodemographic factors. Improving portal enrollment and frequency of use may be critical for symptom management interventions deployed via patient portals.